2021
DOI: 10.1007/s13304-021-00991-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of trauma admissions in a level 1 trauma center in Northern Italy: a nine-year study

Abstract: The aim of this study was to analyze the results of 9 years of trauma care and data collection in a level 1 urban trauma center in Northern Italy. Overall, 6065 patients have been included in the study; the number of patients managed yearly has doubled between 2011 and 2019. This rise mostly involved patients with injury severity score (ISS) < 16. Most injuries (94%) were blunt. Road traffic accidents, especially involving motorcycles, were the most common cause of injury. Self-inflicted injuries were respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
9
1
Order By: Relevance
“…In contrast with North American Literature [ 7 , 20 ], GSW and SW represented a minor cause of death in our sample: penetrating injuries represented only approximately 8% of all injuries, and most GSWs were self-inflicted in male patients > 40 years of age. These results were in line with the overall trauma trends, as the incidence of this type of MOIs is higher in North America than in Europe [ 11 , 20 ]. Our study was conducted in a high-flow Level One trauma center and showed, for the first time in Italy, the potential role of a specialized and trained Trauma Team in reducing mortality.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast with North American Literature [ 7 , 20 ], GSW and SW represented a minor cause of death in our sample: penetrating injuries represented only approximately 8% of all injuries, and most GSWs were self-inflicted in male patients > 40 years of age. These results were in line with the overall trauma trends, as the incidence of this type of MOIs is higher in North America than in Europe [ 11 , 20 ]. Our study was conducted in a high-flow Level One trauma center and showed, for the first time in Italy, the potential role of a specialized and trained Trauma Team in reducing mortality.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the study was a retrospective analysis of a nine-year cohort of trauma patients transported and treated in a level one trauma center: a high-flow trauma center with a surgical leadership in trauma management and a staff specifically trained on trauma management and damage-control procedures [ 11 , 21 ]. Although it represented the first Italian report on the topic, it cannot reflect the overall mortality distribution of trauma patients in all the country, as there are differences in trauma management according to the center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(69.5%) and followed by falls (12.3%) [ 15 ]. The study of Pogorzelski et al, in Brazilian people pointed out that 60.4% of trauma patients suffered RTAs (52% motorcycle), and 31.2% were violence victims [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chest trauma represents one of the leading causes of morbidity and the second cause of death in patients with multiple trauma, followed only by head injuries [ 1 ]. The correct in-hospital management of chest trauma seems to be of paramount importance to improve patients’ outcomes and decrease the length of stay (LOS) [ 2 ]. The proper use of ventilation supports plays a fundamental role in patient management, ensuring the appropriate thoracic expansion and potentially avoiding the development of respiratory complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%